The clinical feature of myocilin Y437H mutation in a Chinese family with primary open-angle glaucoma. Issue 10 (5th January 2019) - Lei, Lei; Li, Shushan; Liu, Xiangyun; Zhang, Chun
Abstract : Purpose: To characterise the genotype(s), phenotype(s) and age-related penetrance of glaucoma in a Chinese family with primary open-angle glaucoma (POAG). Methods: Recruited from a Chinese family spanning four generations, 7 individuals with POAG, 1 with ocular hypertension (OHT) and 14 unaffected individuals were included in this study. Genotypic investigation included sequencing of mutation sites using a glaucoma panel in combination with high-throughput sequencing and validated using Sanger sequencing. Phenotypic characterisation included investigation into patient medical history and physical examination. Results: Eight (36.4%) family members harboured heterozygous Y437H mutation, of whom seven (87.5%) were glaucomatous and one (12.5%) had OHT. The mean age of POAG diagnosis was 30.85±7.13 years. The mean highest recorded intraocular pressure (IOP) was 46.57±6.53 mm Hg. They all had complained of symptoms associated with vision and pain. Four (57.1%) patients presented blindness. Five eyes (62.5%) presented with severe and three eyes with moderate visual field defects. Most of them underwent surgery on average 1.29±2.36 years after diagnosis, and the mean IOP at study was 17.95±7.23 mm Hg, with an average of 0.92±0.86 eye-drops. The patient with OHT was treated with latanoprost only and her IOP was well controlled. Age-related glaucoma penetrance was 0% in individuals under the age of 20 years, 50% at ages 20–35 years, 75% at ages 31–35 years and 87.5% over 45 years. Conclusion: A novel MYOC mutation (c.1309T>C, p.Y437H) in a Chinese family with POAG was identified which was associated with a phenotype characterised by severe visual impairment, frequent surgical intervention requirement and relatively high penetrance.